SOCIAL MEDIA ANALYSIS OF CONTRACEPTIVE (CONDOM) USE POLICY FOR STUDENTS AND TEENAGERS IN INDONESIA - Bayu Aulia Priyantomo (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The development of technology, especially in social media, is increasingly developing every year, which is commonly used daily by the public with the aim of obtaining information. The approach used in this study is the Social Media Analytics (SMA) framework to analyze sentiment using NoLimit Indonesia software. Sentiment Analysis is a measurement of sentiment or emotion of social media users based on content analysis (positive/negative/neutral). This study aims to determine the sentiment analysis using the keywords "contraceptives" and "condoms" on the opinions of social media users regarding the policy of using contraceptives for students and adolescents with a period of one week. The results showed that neutral sentiment was 6,232 X account users, negative sentiment was 359 X account users, and 86 X account users were in a negative position. The conclusion of the study is that the response of social media X users was more neutral at 93%, 5.4% negative and 1.3% positive towards the policy on the use of contraceptives for teenagers or students in regulation 28 of 2024 concerning the Implementing Regulations of Law (UU) Number 17 concerning health which includes several health programs including in the reproductive system in article 103, especially in paragraph (4) point e, namely the provision of contraceptives, this is what is problematic and invites public attention.